Monocytes acquire prostate cancer specific chromatin conformations upon indirect co-culture with prostate cancer cells - Alshaker, Heba; Hunter, Ewan; Salter, Matthew; Ramadass, Aroul; Westra, Willem; Winkler, Mathias; Green, Jayne; Akoulitchev, Alexandre; Pchejetski, Dmitri (Frontiers in Oncology, 2022)
Background: Dynamic multi-layered chromosomal loop interactions are powerful regulators of gene expression. Chromosome structures undergo early changes during tumourigenesis both in tumour and in circulating cells and can serve as a disease biomarker. We have recently detected specific chromosome conformations in circulating cells of patients with prostate cancer that were similar to ones found in their primary tumours, however the possibility of horizontal transfer of chromosome conformations was previously not studied. Methods: U937 human monocytes were co-cultured in Boyden chambers through 0.45uM membrane with or without PC-3 human prostate cancer cells or their conditioned media and a custom DNA microarray for 900,000 chromosomal loops covering all coding loci and ncRNA genes was performed on each part of the co-culture system. Results: We have detected 685 PC-3 cell-specific chromosome conformations across the whole genome that were absent in naïve monocytes but appeared in monocytes co-cultured with PC-3 cells or with PC-3-conditioned media. Similarly, 122 monocyte-specific conformations appeared in PC-3 cells upon co-culture. Comparing PC3-specific conformations to the ones we have previously detected in systemic circulation of high-risk prostate cancer patients revealed 9 Positive loops present both in vitro and in high-risk prostate cancer patients. Conclusions: Our results demonstrate for the first time the proof of concept of horizontal transfer of chromosome conformations without direct cell-cell contact. This carries high clinical relevance as we have previously observed in circulating cells of patients with melanoma and prostate cancer chromatin conformations similar to ones in their primary tumours. These changes can be used as highly specific biomarkers for diagnosis and prognosis. Further studies are required to elucidate specific mechanism of chromosome conformations transfer and its clinical significance in particular diseases.